Análise comparativa da anodização eletroquímica para obtenção de nanotubos de titânia em substratos α-Ti e β-TiNi - Pedro Damas Resende (2020)
Titanium and its alloys are widely explored in science and technological applications due to its intrinsic characteristics of high mechanical and corrosion resistance, biocompatibility, catalytical properties, among others. Many of these applications are suitable due to the natural titania coat that forms on top of the base metal, which makes its morphology control a primary concern. Several surface finishing techniques have been proposed throughout the years to achieve this goal, since mechanical or chemical to optical processes. Electrochemical processes are efficient ways to functionalize the surface of a base metal once they have relatively easy operational control, are cost-effective, are reproducible and are easy to apply even in complex-shaped pieces. Nanotubular titania films obtained by electrochemical anodization are widely explored in the literature for commercialy pure titanium or mostly α alloys. There is a lack of comprehension how these processes can be used to produce the same kind of nanostructures in pure β alloys. One example of exclusively β alloy is the TiNi phase, which was used to better understand the mechanisms involved in its eletrochemical anodization. Commercially pure titanium and TiNi strips were used in this work. Both materials had its structure determined by X-Ray diffraction and were characterized prior to the electrochemical anodization as well as after the anodic process. The samples were anodized in a electrolyte with a composition of 0,2%m. NH4F, 1%v. H2O in ethyleneglycol. The chosen anodization potentials were 5, 15, 25, 45 and 60 V. The process was set to have 3 hours of duration. The samples were characterized by scanning electron microscopy and its morphological features were assessed by a difital image analyzer. All anodization conditions lead to the formation of nanotubular titania in commercially pure titanium. The same behavior was not observed for TiNi alloys, as the only condition that produced an uniform anodic film was at the anodization potential of 5 V. As the potential increased to 15 and 25 V the degree of organization of the nanostructures was lost and some tubular structures could be observed in a spongy-like oxide matrix. TiNi samples anodized at 45 and 60 V undergone severe corrosion damage and no nanotube formation could be observed. The growth mechanisms of the anodic films seem to be similar for both kinds of substrates, but the result of the TiNi metal/oxide interface has lower degree of organization. It can be concluded that the growth of titania nanotubes in TiNi substrates is feasible as it is in pure titanium substrate. But it is important to choose the anodization potential carefully because the anodic film produced on top of TiNi samples is more prone to suffer degradation from the anodic process du to its higher reactivity.